Isolated Ocular Manifestation of Relapsed Chronic Myelogenous Leukemia Presenting as Myeloid Blast Crisis in a Patient on Imatinib Therapy: A Case Report and Review of the Literature. (24th December 2015) - Gulati, Rohit; Alkhatib, Yaser; Donthireddy, Vijayalakshmi; Felicella, Michelle Madden; Menon, Madhu P.; Inamdar, Kedar V.
Abstract : Blast phase in chronic myelogenous leukemia (CML) has rarely been reported to involve extramedullary sites like skin, lymph nodes, and central nervous system. Clinical history, characteristic hematologic findings (elevated leukocyte counts, myelocytic predominance, and basophilia), and Philadelphia chromosome are of high diagnostic significance especially in isolated extramedullary presentations. We describe a unique case of CML relapse with blast phase involving the eye. A 66-year-old man with a known diagnosis of CML on imatinib and in molecular remission for 3 years presented with a painful blind eye. Histologic examination revealed diffuse involvement of choroid, iris, vitreous humor, and the optic nerve by blast cells. The blasts expressed CD34, aberrant TdT, and a myeloid phenotype (CD13, CD33, and CD117). Fluorescence in situ hybridization (FISH) of vitreous fluid detected BCR-ABL1 gene rearrangement. Additionally, trisomy 8 and gains of 9 and 22 were seen which were not present in the initial diagnostic marrow study 3 years ago. At relapse, the bone marrow, peripheral blood, and the cerebrospinal fluid were not involved by CML. Patient received induction chemotherapy and single dose prophylactic intrathecal methotrexate and was maintained on antityrosine kinase therapy and eventually underwent allogenic stem cell transplantation.